Determinants affecting customer perceived e-service quality towards e-retailing shopping site in Malaysia - Bakri, Mohammed Hariri; Lim, Pei Sian; Habidin, Nurul Fadly; Abdul Aziz, Nor Azah; Masrom, Nor Ratna (Inderscience Enterprises Ltd., 2021)
In the current new era of digital, e-commerce platform has been growing rapidly. Thus, this research aimed to study the determinants affecting customer perceived e-service quality (PeSQ) towards e-retailing shopping site in Malaysia and to examine the most significant determinants of e-service quality towards customer PeSQ from e-retailing shopping site in Malaysia. In order to study this, the researchers have selected 384 respondents as sample using Google Form questionnaire distributed online. For the finding analysis, the researcher used SPSS software with explanatory factor analysis test of the data. It depicted that there were exactly five factors extracted in the research. Multiple regression tests were used to find the most significant factor. The results showed that privacy as the most significant predictor but reliability was not significant in the research.